Experiential Economic Education: An Analysis of Economic Self-Reliance Values in Student Cooperative Activities at the Senior High School Level - Aulia, Hanayatul; Yaqutunnafis, Lale; Hully, Hully (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study explores how experiential economic education contributes to the development of economic self-reliance values through student cooperative activities at the senior high school level. Employing a qualitative descriptive method, data were gathered via interviews, observations, and documentation involving students, cooperative advisors, and school staff. The findings show that student cooperatives serve as real-life laboratories where students engage in various economic practices such as planning, budgeting, marketing, sales, and bookkeeping. These activities provide opportunities for students to internalize values of independence, responsibility, discipline, initiative, and entrepreneurship. The cooperative functions not only as an extracurricular program but also as a meaningful educational space that bridges economic theory with practical experience. The study concludes that integrating cooperative-based experiential learning in schools significantly enhances students’ economic literacy and nurtures.